Online hotel reservations: accessing factors influencing customers attitude and behaviours / Jazira Anuar ... [et al.] - Anuar, Jazira; Musa, Mushaireen; Khalid, Khazainah; Abu Bakar, Siti Khuzaimah; Abd. Majid, Hayati Adilin (2018)
The booming trends of hotel online reservations worldwide had influenced many hotels to establish online purchasing. Malaysia hotel industry had also grabbing the opportunity of this current trend by establishing online purchasing at their hotel. This research paper is focus on the factors that influence customer’s attitudes and purchasing behaviour in online purchasing, namely; information, trust, price and convenience. Aditionally, this study identifies the influential and popular factor among four factors mentioned above. Secondary data is used in order to complete the objectives of the study. It provides quality and impactful research through the deeper exploitation of major data resources readily available from various sources. Many commentators in this field unanimously agreed that online purchasing significantly contributes to the prosperity of the hotel business as well as engaging customers to do repeat purchase. This is proven as various hotels are adopting online purchasing which can be seen in several industries too including retail shopping, supermarkets, transportation, telecommunication as well as food business. Price appeared to be dominant factor in influencing customer’s online attitudes towards online reservations purchasing behavior. Probably, factors that contribute to the growth of this online purchase were basically comes from the potential of online purchasing as a powerful marketing weapon to attract customers with their purchasing behaviour. Several avenues for future research is discuss at the end of the paper.